CAQK, a peptide associating with extracellular matrix components targets sites of demyelinating injuries - Abi-Ghanem, Charly; Jonnalagadda, Deepa; Chun, Jerold; Kihara, Yasuyuki; Ranscht, Barbara (Frontiers in Cellular Neuroscience, 2022)
The destruction of the myelin sheath that encircles axons leads to impairments of nerve conduction and neuronal dysfunctions. A major demyelinating disorder is multiple sclerosis (MS), a progressively disabling disease in which immune cells attack the myelin. To date, there are no therapies to target selectively myelin lesions, repair the myelin or stop MS progression. Small peptides recognizing epitopes selectively exposed at sites of injury show promise for targeting therapeutics in various pathologies. Here we show the selective homing of the four amino acid peptide, cysteine-alanine-lysine glutamine (CAQK), to sites of demyelinating injuries in three different mouse models. This selective homing was assessed by administrating fluoresceinamine (FAM)-labeled peptide into the blood stream of mice, comparing sites of demyelination with healthy brain or spinal cord tissue. FAM-CAQK selectively targeted demyelinating areas in all three models and was absent from healthy tissue. At lesion sites, the peptide primarily associated with the fibrous extracellular matrix deposited in interstitial spaces proximal to reactive astrocytes. Overlap of FAM-CAQK was detected with Tenascin-C although tenascin depositions made up only a minor portion of the examined lesion sites. In mice on a six-week cuprizone diet, FAM-CAQK peptide crossed the nearly intact blood-brain barrier and homed to demyelinating fiber tracts. These results demonstrate the selective targeting of CAQK to demyelinating injuries under multiple conditions and confirm the previously reported association with the ECM (Mann et al., 2016). This work sets the stage for further developing CAQK peptide targeting for diagnostic and therapeutic applications aimed at localized myelin repair.